Control of Varroa destructor mites in capped worker brood cells by using formic acid and thymol in africanized honey bee colonies under tropical conditions. A technical note - Ramírez, Marianyela (2017)
The mortality of the Varroa destructor mite was evaluated in capped worker brood cells by using formic acid and thymol in Africanized honey bee colonies. The apiary was located in Atenas, Alajuela, Costa Rica, and was randomly arranged in three groups: A, B and C. Group A was treated with 150 g formic acid at 65%, while group B received two applications of 25 g thymol, and group C was used as a control group. Mortality of the Varroa’s different stages was evaluated in capped worker brood cells by checking the pupa and the bottom of the cell for mites. Eighty-six percent mite mortality occurred in capped brood cells in colonies treated with formic acid, while Varroa mortality was less than 10% in capped cells for control colonies and colonies treated with thymol. In conclusion, high mortality of Varroa mites was observed in capped brood cells after applying formic acid, while mortality was low in control colonies and colonies treated with thymol. The foregoing could imply a direct effect of formic acid over mites in capped brood cells.